2017
DOI: 10.1515/probus-2016-0016
|View full text |Cite
|
Sign up to set email alerts
|

Stressed postverbal pronominals in Catalan

Abstract: Majorcan Catalan postverbal pronominal elements are typically described as being prominent due to stress shift from their host. This study sheds light on the prosodic phonology of these pronouns through the analysis of duration, vowel quality, and f0 in verb + pronominal sequences, which are compared to a baseline condition without pronominals and to the same sequences in a Catalan variety without stress shift. Our results show acoustic differences in the realization of pronominals in these varieties. The dura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 33 publications
2
4
0
Order By: Relevance
“…The studies that we have just reviewed have revealed that Romance varieties differ in the relative prominence patterns associated with verbs and pronouns in verb+clitic sequences. Acoustic studies have shown that when the stress is perceived to be on the clitic, duration is affected (Colantoni & Cuervo 2013;Kim & Repetti 2013;Nadeu et al 2017) and pitch patterns may also differ from the patterns found in cases where the clitic is unstressed (Kim & Repetti 2013;Nadeu et al 2017). This body of experimental evidence is consistent with early reports of doubly accented clitics in 16th century Spanish poetry and in literary and popular Argentine texts, where the orthographic accent is written on the clitic.…”
Section: Stress Shift In Verb+clitic Sequences and The Formation Of Tsupporting
confidence: 83%
See 3 more Smart Citations
“…The studies that we have just reviewed have revealed that Romance varieties differ in the relative prominence patterns associated with verbs and pronouns in verb+clitic sequences. Acoustic studies have shown that when the stress is perceived to be on the clitic, duration is affected (Colantoni & Cuervo 2013;Kim & Repetti 2013;Nadeu et al 2017) and pitch patterns may also differ from the patterns found in cases where the clitic is unstressed (Kim & Repetti 2013;Nadeu et al 2017). This body of experimental evidence is consistent with early reports of doubly accented clitics in 16th century Spanish poetry and in literary and popular Argentine texts, where the orthographic accent is written on the clitic.…”
Section: Stress Shift In Verb+clitic Sequences and The Formation Of Tsupporting
confidence: 83%
“…A recent analysis of Majorcan Catalan (Nadeu et al 2017), a variety in which final stressed clitics had been reported, also found evidence consistent with the claim that the clitic bears primary rather than secondary stress in this Catalan variety. In their study, 8 speakers of Central Catalan, a variety with no ESS, and Majorcan Catalan, which is reported to have ESS, were compared in their production of verb+clitic and verb+non-clitic pronoun sequences using a reading task.…”
Section: Prominence and Cliticizationsupporting
confidence: 57%
See 2 more Smart Citations
“…Some examples of stress shift in Majorcan Catalan appear in (1) with one enclitic in (1a,b) and two enclitics in (1c). Vowel reduction to schwa in the verb further demonstrates that stress shifts in forms with enclisis (see also Nadeu et al 2016). The same stress patterns are found in Minorcan Catalan, not exemplified in (1).…”
Section: Stress In Verb-clitic Structures In Catalanmentioning
confidence: 56%